The Effect of Entrepreneurial Orientation on Entrepreneurial Intention (Global Journal of Management and Business Research, 2025)
Abstract- Objective This study aims to investigate the influence of entrepreneurial orientation innovativeness pro-activeness and risk-taking on entrepreneurial intention through the mediating variables of family business involvement personal attitudes social norms and perceived behavioral control Design methodology approach Primary data were collected using questionnaires This study analyzed 445 valid responses from Egyptian enterprises The hypotheses were analyzed through correlation and structural equation modeling Findings The results of the analysis fully support the relationship between entrepreneurial orientation and personal attitude family business involvement and entrepreneurial intention personal attitude and entrepreneurial intention and social norms and entrepreneurial intention In addition the results partially support the relationship between entrepreneurial orientation family business involvement social norms perceived behavioral control and between entrepreneurial orientation and intention However the analysis did not support the relationship between perceived behavioral control and entrepreneurial intention
Keywords: Keywords: entrepreneurial orientation; entrepreneurial intention; family business involvement